Budesonide MMX in the Treatment of Ulcerative Colitis: Current Perspectives on Efficacy and Safety - Maconi G; Camatta D; Cannatelli R; Ferretti F; Carvalhas Gabrielli A; Ardizzone S (Dove Medical Press, 2021)
Giovanni Maconi, Deborah Camatta, Rosanna Cannatelli, Francesca Ferretti, Anna Carvalhas Gabrielli, Sandro Ardizzone Gastroenterology Unit, Department of Biomedical and Clinical Sciences FBF – L.Sacco, University Hospital, Milan, ItalyCorrespondence: Giovanni MaconiGastroenterology Unit, Department of Biomedical and Clinical Sciences, ASST Fatebenefratelli-Sacco University Hospital, University of Milan, ItalyTel +39 02 39043164Fax +39 02 39042232Correspondence Email giovanni.maconi@unimi.itAbstract: Budesonide MMX is a low bioavailability corticosteroid oral once-daily formulation, which has a controlled rate of release throughout the colon, thanks to the multimatrix (MMX) formulation. It has been available for a decade in the USA and Europe for the induction of remission in patients with active, mild to moderate ulcerative colitis, particularly for those not responsive to mesalamine. The efficacy of budesonide MMX in this setting has been assessed by registrative randomized controlled trials showing a higher rate of clinical and endoscopic remission at 8 weeks compared with placebo, mostly in patients with proctosigmoiditis and left-side colitis. Since it is available in our therapeutic armamentarium, a few studies have confirmed the effectiveness of budesonide MMX also in real-life, highlighting the high rate of clinical response and remission and the high safety profile. In the present review, we summarise clinical trials and real-life results of budesonide MMX, assessing its use and predictors of response and non-response in real-life.Keywords: budesonide MMX, ulcerative colitis, efficacy, effectiveness, safety